Penyusunan CPL Berbasis Kkni Level 8 Dan Visi Prodi Magister Pendidikan Agama Islam Melalui Analisis RPS Mata Kuliah Sejarah Sosial Pendidikan Islam - Adinda Suhaibah; Siti Halimah; Kiki Tandra Pranata; Rahmad Nasution (Simpati, 2026)
This study aims to analyze the formulation of Graduate Learning Outcomes (GLOs) based on the Indonesian National Qualifications Framework (KKNI) Level 8 and their alignment with the vision of the Master’s Program in Islamic Education through an analysis of the Semester Learning Plan (RPS) for the Social History of Islamic Education course. The research employed a qualitative approach using Critical Discourse Analysis (CDA) on curriculum documents, including graduate learning outcomes, the study program vision, and the RPS. The findings reveal that the RPS contains systematic learning components that support the development of students’ critical thinking, analytical skills, and religious values. Its alignment with KKNI Level 8 is reflected in theoretical mastery, analytical competence, and active learning strategies through discussions and academic studies. However, the implementation of research-based learning, transdisciplinary approaches, and innovative scientific work remains suboptimal. Furthermore, the integration among GLOs, Course Learning Outcomes (CLOs), learning methods, and assessment systems requires further strengthening to better support graduate competencies at the master’s level. This study proposes revised GLO formulations emphasizing research-based knowledge development, multidisciplinary problem-solving skills, academic professionalism, and Islamic character. These findings are expected to contribute to curriculum evaluation and development in the Master’s Program in Islamic Education to ensure greater relevance to KKNI Level 8 standards and the contemporary needs of Islamic education.